Komunikasi NonVerbal Dalam Praktik Peradilan Pidana Dengan Kewenangan Melakukan Interpretasi Hukum - Rocky Marbun (Kertha Wicaksana, 2021)
The logical consequence of submitting to the civil law system - one of which is paper working or administrative mindedness. As characterized by Article 75 of the Criminal Procedure Code, that is, every legal action must be in the form of an Investigation Report (BAP). Thus, a BAP is a legal document that contains information for Law Enforcement Officials (APH) to obtain a description of a criminal event. Normative Legal Studies, in essence, focus on APH activities to interpret legal documents in order to be able to bring up a legal decision. Thus, legal practitioners and academics forget about the ability of APH as an ordinary human being who can build a non-verbal communication in relation to the legal decisions it will make. Therefore, this study focuses on a form of non-verbal communication that has an influence on the praxis realm of legal science, namely by asking the problem is "how is the influence of non-verbal communication in the criminal justice process on the Criminal Justice System in Indonesia?" In order to answer this problem, the researcher used the Normative Juridical Research Method as a logical consequence in law based on secondary data through library research. In order to complement this research, the researcher used several models of research approaches, namely the philosophical approach, the semiotic approach, and the hermeneutic approach, with the analysis method being qualitative analysis. The results of the study indicate that there are efforts to marginalize legal interpretation as a basis for making decisions, by promoting non-verbal communication in criminal justice practices.